Effect of laparoscopic ovarian drilling on ovulation rate in women with clomiphene resistant polycystic ovarian syndrome - Sana Ansari; Reena Yadav; Nishtha Jaiswal (Barpeta Obstetrics and Gynaecological Society, 2023)
Background: Laparoscopic ovarian drilling (LOD) is a surgical treatment that can stimulate ovulation in women diagnosed with polycystic ovarian syndrome (PCOS) and especially those with resistance to clomiphene citrate (CC). Objective: To observe the effect of LOD on ovulation rate in women with PCOS. Methods: The study included thirty CC resistant PCOS women between 20-35 years of age, trying for conception, with patent bilateral fallopian tubes and male factor infertility ruled out. Hormone levels including serum LH, FSH and testosterone were tested on day 2/3 of menstrual cycle before and 1 month after LOD. Patients underwent LOD in between 5th -9th day of the cycle. During the procedure each ovary was drilled using monopolar cautery of 40 W of power at 4 sites, 4mm deep, for 4 seconds. Spontaneous ovulation rate was noted by follicular monitoring done by transvaginal sonography following LOD in the next two menstrual cycles. Results: It was observed that serum testosterone levels reduced from 46.56 ± 24.06 ng/dl before LOD to 35.02 ± 19.85 ng/dl after LOD and 80% PCOS women ovulated after ovarian drilling (i.e., 24 out of 30 cases). 8 women conceived following LOD making the cumulative pregnancy rate of 33.33%. Conclusions: LOD induces ovulation in PCOS women resistant to CC due to decreasing testosterone levels as seen in this study. So prior to initiation of gonadotropin therapy for CC resistant PCOS, LOD may be used as an alternative treatment in such cases.